The Global Burden of Surgical Disease: An Analysis of Inaccessible Surgical Care in Low and Middle Income Countries - Huynh, Chau; Huynh, Minh N. Q. (Université d'Ottawa | University of Ottawa, 2018)
Worldwide, 4.8 billion people do not have access to safe, adequate surgical care and an-aesthetic management. Surgical care has been deemed “the neglected child of global health,” a startling reminder of the disparities in health services. The provision of surgi-cal interventions can avert 11% of the global burden of disease and 1.5 million deaths each year. Many obstacles exist for low- and middle-income countries (LMIC) to pro-gress towards accessible surgical care. The first challenge is delivering cost-effective sur-gical care despite financial constraints and political turmoil. Foreign aid was established to alleviate the financial burden and its contributions have been pivotal. However, based on the political climate in certain countries, funds are siphoned to government sectors other than health care. Moreover, the lack of infrastructure, equipment, and personnel in LMIC compound the issue. The other challenge is determining if surgery is as feasible and effective as non-surgical health interventions. Surgical care is crucial and this paper aims to assess the challenges that limit its stature in global health discussions. The paper will address the influence of financing, infrastructure, workforce, service delivery, and information management on surgical care, and the current resolutions, such as humanitarian aid missions.
Keywords: health services; low- and middle-income countries; surgery